Key characteristics for sustainable sugarcane: A community enterprise in Khon Kaen Province, Thailand - Utaranakorn, Panatda; Kiatmanaroach, Teera (Kasetsart Journal of Social Sciences, 2021)
This research aimed to identify the key characteristics that facilitate effective management performance; and to analyze the internal and external environmental factors of a sugarcane community enterprise in Khon Kaen Province, in Northeastern Thailand. The results indicated that the key characteristics were instrumental in the capacity of collecting and supplying sugarcane to reach the enterprise’s yearly quota. The community enterprise also defines how profits and benefits are divided among members. The active internal relationships within the group, called ‘kinship relation’, create a high level of trust, reliability, and honesty; and promote collective responsibility among members. Lastly, annual support from financial institution, namely, credit with low-interest rates, plays an important role in the enterprise’s sustainable performance. To further develop the sugarcane community enterprise and to achieve sustainable performance, we recommend that the committee and members share responsibility with honesty and harmony, plan production to meet annual quotas, divide income and benefits equally, and properly manage the loans and equity provided by financial institutions.